2006
DOI: 10.1073/pnas.0506855103
|View full text |Cite
|
Sign up to set email alerts
|

Probing mucin-type O-linked glycosylation in living animals

Abstract: Changes in O-linked protein glycosylation are known to correlate with disease states but are difficult to monitor in a physiological setting because of a lack of experimental tools. Here, we report a technique for rapid profiling of O-linked glycoproteins in living animals by metabolic labeling with N-azidoacetylgalactosamine (GalNAz) followed by Staudinger ligation with phosphine probes. After injection of mice with a peracetylated form of GalNAz, azide-labeled glycoproteins were observed in a variety of tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
181
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(187 citation statements)
references
References 50 publications
(74 reference statements)
4
181
0
2
Order By: Relevance
“…This unnatural sugar is processed by the GalNAc salvage pathway to form the intermediate uridine diphospho (UDP)-GalNAz, which is recognized by a family of polypeptide GalNAc transferases in the Golgi compartment. Ac 4 GalNAz has been used to label mucin-type O-linked glycans in numerous cell lines, live mice (76), and zebrafish (73).…”
Section: Metabolic Labeling Of Glycan Subtypes With Chemical Reportersmentioning
confidence: 99%
“…This unnatural sugar is processed by the GalNAc salvage pathway to form the intermediate uridine diphospho (UDP)-GalNAz, which is recognized by a family of polypeptide GalNAc transferases in the Golgi compartment. Ac 4 GalNAz has been used to label mucin-type O-linked glycans in numerous cell lines, live mice (76), and zebrafish (73).…”
Section: Metabolic Labeling Of Glycan Subtypes With Chemical Reportersmentioning
confidence: 99%
“…These methods include different bioorthogonal reactions such as ketoneaminooxy/hydrazide ligation (12,13), Staudinger ligation (14), Michael addition (15), and the strain-promoted, and Cu(I)-catalyzed [3 ϩ 2] azide-alkyne cycloaddition (16)(17)(18)(19). Many sugar analogs with small functional handles, including ketones and azides, are tolerated and have been incorporated into glycoconjugates (14,20,21). These reporting sugars have been coupled with various tags such as FLAG peptides, biotin, and fluorescent or fluorogenic molecules.…”
mentioning
confidence: 99%
“…The azide group has been the most widely used reporter group due to its chemical stability, small size and bioorthogonal reactivity with alkynes and Staudinger phosphines. [12][13][14] Other chemical reporters used for metabolic labelling include: alkynes, 15,16 ketones, 17 thiols, 18 cyclopropenes 19,20 and alkenes. 21 We have recently shown that the isonitrile group can also be used as a novel chemical reporter group for glycan metabolic labelling.…”
Section: Introductionmentioning
confidence: 99%
“…19,21 In these two accounts of dual sugar labelling N-acetyl mannosamine was the monosaccharide bearing the cyclopropene 19 or alkene 21 tag. As with per-acetylated N-azidoacetyl mannosamine (Ac 4 ManNAz), 13 these non-natural mannosamine derivatives are incorporated into cell surface glycoproteins as modified terminal sialic acids. The modified sialic acids were then detected using a fluorescent tetrazine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation